Kepuasan Pengguna Sistem Informasi Rekam Medis Elektronik RSUD Tugurejo - Nina Dwi Astuti; Asharul Fahyudi (Jurnal Manajemen Kesehatan Indonesia, 2023)
Evaluation of user satisfaction of Electronic Medical Record (EMR) system users can be considered by hospitals in developing EMR systems.  Tugurejo Hospital has implemented EMR both outpatient and inpatient. Quantitative research is conducted to determine user satisfaction. The respondents were 67 users of EMR from doctors and nurses. EMR user satisfaction according to Delone and McLean's IT/IS Success Model theory was analyzed using SMART-PLS to determine how strong the influence of system quality, information quality and service quality on EMR user satisfaction. The results showed that user satisfaction was influenced by system quality (T-stat = 2.96), information quality (T-stat = 1.66), service quality (T-stat = 1.84). There is a mutual influence between system quality, information quality and service quality on user satisfaction with strong categories (R-square = 0.748).